2013
DOI: 10.1002/cbm.1849
|View full text |Cite
|
Sign up to set email alerts
|

A new interactive computer simulation system for violence risk assessment of mentally disordered violent offenders

Abstract: The use of interactive computer simulation techniques is not only generally acceptable to offender patients, but it also helps to differentiate their current response style to particular circumstances from that of healthy controls in a way that does not rely on their verbal abilities and may tap more effectively into their emotional reactions than standard verbal questions and answer approaches. This may pave the way for Reactions on Display providing a useful complement to traditional risk assessment, and a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…ToM. Five studies (Abu-Akel, 2004;Arborelius et al, 2013;Majorek et al, 2009;Murphy, 1998Murphy, , 2006 examined ToM in VSZ, with three studies comparing to different clinical groups. Arborelius et al (2013) found that VSZ and a violent autism spectrum disorder (ASD) group were less able to attribute appropriate emotions to an individual they viewed in a video-clip and less able to use contextual information to inform these judgements compared to healthy controls.…”
Section: Emotion Recognition Tom and Experience Of Emotion In Violenmentioning
confidence: 99%
See 1 more Smart Citation
“…ToM. Five studies (Abu-Akel, 2004;Arborelius et al, 2013;Majorek et al, 2009;Murphy, 1998Murphy, , 2006 examined ToM in VSZ, with three studies comparing to different clinical groups. Arborelius et al (2013) found that VSZ and a violent autism spectrum disorder (ASD) group were less able to attribute appropriate emotions to an individual they viewed in a video-clip and less able to use contextual information to inform these judgements compared to healthy controls.…”
Section: Emotion Recognition Tom and Experience Of Emotion In Violenmentioning
confidence: 99%
“…Five studies (Abu-Akel, 2004;Arborelius et al, 2013;Majorek et al, 2009;Murphy, 1998Murphy, , 2006 examined ToM in VSZ, with three studies comparing to different clinical groups. Arborelius et al (2013) found that VSZ and a violent autism spectrum disorder (ASD) group were less able to attribute appropriate emotions to an individual they viewed in a video-clip and less able to use contextual information to inform these judgements compared to healthy controls. These results are mirrored in two studies carried out in a forensic hospital (Murphy, 1998(Murphy, , 2006 which demonstrate that VSZ individuals have poorer second-order ToM (Murphy, 1998), are less able to interpret emotional information from the eyes and have poorer performance on ToM tasks (Murphy, 2006) compared to a PD group; however, they did not differ from a violent ASD group.…”
Section: Emotion Recognition Tom and Experience Of Emotion In Violenmentioning
confidence: 99%
“…The goal of this type of technology is to explore attitudes or behavioral responses to offense-related situations that are viewed as realistic and personally relevant by the user. Some studies used videos with real actors and authentic situations in which the user had to decide on behavioral reactions ( 69 , 73 , 74 ), while others simulated situations via virtual embodied conversational agents to conduct a dialog with prisoners ( 71 ), existing popular crime drama series ( 72 ), or VR ( 70 ).…”
Section: Resultsmentioning
confidence: 99%
“…Arborelius et al . () investigated the use of a computer simulation system for risk assessment. They found that the simulated environment was acceptable to service users and discovered differences in response styles between participants with mental disorder and healthy controls.…”
Section: Serious Gamesmentioning
confidence: 99%